Simultaneous Estimation and Validation of Simvastatin and Ezetimibe by HPTLC in Pure and Pharmaceutical Dosage Forms - SHIVSHANKER, K.; SREEKANTH, N.; HARIKRISHNAN, N.; ROOSEWELT, C.; SHANMUGA PANDIYAN, P.; SRINIVASA RAO, G.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance thin layer chromatographic method has been developed and validated for simultaneous estimation of simvastatin and ezetimibe in pure and pharmaceutical dosage form. It was performed on TLC plate precoated with silica gel 60F254 as a stationary phase using mobile phase composing of ethyl acetate:chloroform (80:20) and the detection was carried out in absorbance/reflectance mode at 220 nm showing Rf value 0.76 for simvastatin and 0.89 for ezetimibe. The percentage estimation of labeled claims of simvastatin and ezetimibe from commercial tablet was found to be 99.62, 99.34 by height and 99.40, 99.48 by area, respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. Linearity was observed between 600 and 1400 μg/mL for simvastatin and ezetimibe. The recoveries of drugs by standard addition method were found in the range of 99.73 and 99.59 for both the drugs. The proposed method is precise, accurate and can be used for routine analysis of simvastatin and ezetimibe in tablets.